Magnetic Characteristics of Ni-Filled Luminescent Porous Silicon - Granitzer, Petra; Rumpf, Klemens; Poelt, Peter; Reissner, Michael (Frontiers in Chemistry, 2019)
The aim of the presented work is to combine luminescent porous silicon (PSi) with a ferromagnetic metal (Ni) to modify on the one hand the photoluminescence by the presence of metal deposits and on the other hand to influence the optical properties by an external magnetic field. The optical properties are investigated especially with respect to the wavelength-shift of the photoluminescence due to the metal filling. With increasing metal deposits within PSi the photoluminescence peak is blue-shifted and furthermore an increase of the intensity is observed. Photoluminescence spectra of bare PSi show a maximum around 620 nm whereas in the case of Ni filled samples the peak is blue-shifted to around 580 nm for a deposition time of 15 min. Field dependent magnetic measurements performed with an applied field parallel and perpendicular to the surface, respectively, show a magnetic anisotropy which is in agreement with a thin film. This film-like behavior is caused by the interconnected Ni structures due to the branched porous silicon morphology. The coercivity increases with increasing metal deposition from about 150 Oe to about 450 Oe and also the magnetic anisotropy is enhanced with the growth of metal deposits. Within this work the influence of the magnetic metal filling on the optical properties and the magnetic characterization of the nanocomposites are discussed. The presented systems give not only rise to optoelectronics applications but also to magneto optical integrated devices.